2006
DOI: 10.1007/11775300_23
|View full text |Cite
|
Sign up to set email alerts
|

RecipeCrawler: Collecting Recipe Data from WWW Incrementally

Abstract: Abstract. WWW has posed itself as the largest data repository ever available in the history of humankind. Utilizing the Internet as a data source seems to be natural and many efforts have been made. In this paper we focus on establishing a robust system to collect structured recipe data from the Web incrementally, which, as we believe, is a critical step towards practical, continuous, reliable web data extraction systems and therefore utilizing WWW as data sources for various database applications. The reasons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 15 publications
0
12
0
Order By: Relevance
“…It should be noted that there are various Web-based and software-based approaches that have supported the automated capture of recipe information (Li et al, 2006).…”
Section: Recipe Informationmentioning
confidence: 99%
“…It should be noted that there are various Web-based and software-based approaches that have supported the automated capture of recipe information (Li et al, 2006).…”
Section: Recipe Informationmentioning
confidence: 99%
“…In graphing recipes, Li [10] provided a means to search a recipe database to find similar recipes by structure rather than text and Makino [13] showed that sub-recipes can be identified, extracted and recombined to form new recipes.…”
Section: Recipe Graphsmentioning
confidence: 99%
“…[10,13] suggest that shorter steps will be easier to follow than the traditional long paragraph form of recipes. But in this study 5 cooks said they liked the longer steps of the control condition.…”
Section: Segmentation Of Recipe Stepsmentioning
confidence: 99%
“…In this paper, we explore the features of a Chinese recipe database, in which recipes are crawled from the Web by our RecipeCrawler [11]. To solve the long-standing retrieval problem on Chinese Web, we propose a framework to consider documents by their inner relationship or, in other words, inter-structural similarity.…”
Section: Our Contributionsmentioning
confidence: 99%
“…Table 1 shows a cooking procedure of recipe 'Hu Die Gu' (蝴蝶骨) in Chinese (translated as 'Braised Spare Ribs' in English) crawled by our RecipeCrawler [11]. The cooking procedure is parsed into basic actions and their related properties as discussed in [19].…”
Section: Recipe Model Simplifiedmentioning
confidence: 99%